APPLICATION OF COMPETENCE MODEL «INNOVATION INTELLIGENCE» IN HIGH-TECH INDUSTRIES MANAGEMENT SYSTEM - E. S. Fedorova; N. V. Lashmanova (Дискурс, 2017)
The article highlights the main features of management of innovative companies. The necessity to develop adaptive approaches to organization of personnel training process is proved, which take into account the specific character of high-tech industry and the role of technical knowledge. A competence model is proposed which reflects basic requirements to professional and business knowledge and skills of human resources of innovative companies. The concept of innovation environment as a major influencing factor in the system of training and human resources development is revealed.